NMR and TRLFS studies of Ln(iii) and An(iii) C5-BPP complexes. Issue 2 (19th December 2014) - Adam, Christian; Beele, Björn B.; Geist, Andreas; Müllich, Udo; Kaden, Peter; Panak, Petra J.
Abstract : NMR investigations of Am(C5-BPP)3 3+ show weak paramagnetism in Am(iii ), indicating significant covalence in metal–ligand bonds with N-donor ligands. This may explain the observed extraction selectivity for actinides over lanthanides. Abstract : C5-BPP is a highly efficient N-donor ligand for the separation of trivalent actinides, An(iii ), from trivalent lanthanides, Ln(iii ). The molecular origin of the selectivity of C5-BPP and many other N-donor ligands of the BTP-type is still not entirely understood. We present here the first NMR studies on C5-BPP Ln(iii ) and An(iii ) complexes. C5-BPP is synthesized with 10% 15 N labeling and characterized by NMR and LIFDI-MS methods. 15 N NMR spectroscopy gives a detailed insight into the bonding of C5-BPP with lanthanides and Am(iii ) as a representative for trivalent actinide cations, revealing significant differences in 15 N chemical shift for coordinating nitrogen atoms compared to Ln(iii ) complexes. The temperature dependence of NMR chemical shifts observed for the Am(iii ) complex indicates a weak paramagnetism. This as well as the observed large chemical shift for coordinating nitrogen atoms show that metal–ligand bonding in Am(C5-BPP)3 has a larger share of covalence than in lanthanide complexes, confirming earlier studies. The Am(C5-BPP)3 NMR sample is furthermore spiked with Cm(iii ) and characterized by time-resolved laser fluorescence spectroscopy (TRLFS), yielding important information on the speciation of trace amounts of minor complex species.